STM Observation of the Si(111) - (7×7) Reconstructed Surface Modified by Excess Phosphorus Doping - Hirulak D. Siriwardena; Toru Yamashita; Masaru Shimomura (International Journal of Electrical and Computer Engineering (IJECE), 2017)
The electronic properties of semiconductor surfaces change readily upon changing the carrier densities by controlling the dopant concentration. Additionally, excess dopant atoms can exert electric field which would affect the molecular adsorption process and could be used to manipulate the dynamic movement of confined molecules. A mechanism can be developed to control the molecular dynamic movement on modified semiconductor surface by dopants thus changing the effect of the electric field on the active molecules.  In this study, the Si(111) surface was doped with phosphorus excessively using thermal diffusion process. The surface was then reconstructed to the 7 × 7 configuration via heating under UHV conditions and then studied through STM and STS techniques. The protrusions due to surface and subsurface P atoms appear brighter due to the lone electron pair. The 7 × 7 reconstruction would be destabilized after a critical P substitution of Si-adatom concentration due to high surface strain result in P-terminated (6√3 × 6√3)R30º reconstruction.